Association of maternal obesity and gestational weight gain with adverse maternal and perinatal outcomes - Kurrat-Ul-Aaien; Maham Sultan; Shazia Tufail; Nilofar Mustafa; Humaira Tabassum; Quratul Ain Mushtaq (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the association of maternal obesity and gestational weight gain with adverse maternal and perinatal outcomes. Method: The prospective, cross-sectional study was conducted from April 2023 to February 2024 at the Combined Military Hospital, Lahore, Pakistan, and comprised adult pregnant females carrying singleton pregnancy of any gestational age who had record available for weight at the first antenatal visit in the first trimester. Maternal body mass index at the first antenatal visit was calculated and the subjects were categorised as underweight, normal-weight, overweight and obese. Total weight gain during pregnancy was calculated at the last antenatal visit before delivery. Maternal and neonatal outcomes were observed for obese, overweight and those with >10kg gestational weight gain. Data was analysed using SPSS 26. Results: Of the 151 female subjects with mean age Mean age was 27.48±5.001 years, 102(67.5%) were either underweight or normal-weight, and 49(32.5%) were either overweight or obese. Besides, gestational weight gain was <10kg in 83(55%) cases and >10kg in 68(45%). Preeclampsia had a significant association with body mass index (p=0.003), while gestational age at delivery (p=0.049), neonatal birthweight (p=0.042) and Appearance-Pulse-Grimace-Activity-Respiration score at 5 minutes (p=0.003) were significantly associated with gestational weight gain. Conclusion: Increased maternal body mass index and gestational weight gain were found to be associated with pre-eclampsia, gestational age at delivery, neonatal birthweight and Appearance-Pulse-Grimace-Activity-Respiration score. Key Words: Gestational weight gain, Obesity, Pre-eclampsia, Pregnancy complications.